2020
DOI: 10.1055/s-0040-1712964
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Morbidities, and Developmental Outcomes among Low Birth Weight Infants with Congenital Heart Defects

Abstract: Objective Prematurity and low birth weight (LBW) are risk factors for increased morbidity and mortality in infants with congenital heart defects (CHDs). We sought to describe survival, inhospital morbidities, and 2-year neurodevelopmental follow-up in LBW infants with CHD. Study Design We included infants with birth weight (BW) <2,500 g diagnosed with CHD (except isolated patent ductus arteriosus) admitted January 2013 to March 2016 to a single level-IV academic neonatal intensive care unit. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…We observed that the overall prevalence of CHD was 8.44 per 1,000 live births, and the three subtypes with the highest prevalence of CHD were ASD, VSD, and PFO, which was similar to most of the previous studies (8–10 per 1,000 births at global and local levels) ( 17 – 21 ). The prevalence of CHD in VLBW, LBW, and SGA infants was higher than in other birth weight groups, which was consistent with previous studies ( 2 , 6 8 ), but the prevalence varied slightly in different regions; the reasons why heterogeneity of CHD prevalence might be differences in study populations, prenatal detection capability, and ascertainment of criteria. The reasons for the increased frequency of CHD in VLBW and SGA infants are still a matter of speculation ( 22 ), small septal defects may close spontaneously in utero, and therefore fewer may be apparent in term infants ( 7 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that the overall prevalence of CHD was 8.44 per 1,000 live births, and the three subtypes with the highest prevalence of CHD were ASD, VSD, and PFO, which was similar to most of the previous studies (8–10 per 1,000 births at global and local levels) ( 17 – 21 ). The prevalence of CHD in VLBW, LBW, and SGA infants was higher than in other birth weight groups, which was consistent with previous studies ( 2 , 6 8 ), but the prevalence varied slightly in different regions; the reasons why heterogeneity of CHD prevalence might be differences in study populations, prenatal detection capability, and ascertainment of criteria. The reasons for the increased frequency of CHD in VLBW and SGA infants are still a matter of speculation ( 22 ), small septal defects may close spontaneously in utero, and therefore fewer may be apparent in term infants ( 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…CHDs that caused a decrement in birth weight in a descending order of severity are atrial septal defect (721 g/23%), patent ductus arteriosus (669 g/21%), ventricular septal defect (610 g/19%), pulmonary stenosis (548 g/13%), and tetralogy of Fallot (248 g/8%) ( 5 ). In addition, the prevalence of CHD in very premature/VLBW infants is higher than that of general live births, and it is independent of other risk factors and causes death and serious complications ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Рождение детей с малой массой тела в индустриально развитых странах обусловлено генотипом матери и плода, хронической патологией женщины, особенностями плацентации, осложненным течением беременности, курением, реже -нарушениями питания женщины. В настоящее время большинство исследователей констатируют, что малый вес при рождении является ведущей причиной неблагоприятных перинатальных исходов и тесно связан с неонатальными заболеваемостью, смертностью и выживаемостью [11][12][13][14][15][16]. Доказана ассоциация НМТ при рождении с нарушением физического, моторного и когнитивного развития в последующие периоды детства [17,18].…”
Section:  введениеunclassified